Promoting Apoptosis, a Promising Way to Treat Breast Cancer With Natural Products: A Comprehensive Review - Yuan, Lie; Cai, Yongqing; Zhang, Liang; Liu, Sijia; Li, Pan; Li, Xiaoli (Frontiers in Pharmacology, 2022)
Breast cancer is one of the top-ranked malignant carcinomas associated with morbidity and mortality in women worldwide. Chemotherapy is one of the main approaches to breast cancer treatment. Breast cancer initially responds to traditional first and second-line drugs (aromatase inhibitor, tamoxifen, and carboplatin), but eventually acquire resistance, and certain patients relapse within 5 years. Chemotherapeutic drugs also have obvious toxic effects. In recent years, natural products have been widely used in breast cancer research because of their low side effects, low toxicity and good efficacy based on their multi-target therapy. Apoptosis, a programmed cell death, occurs as a normal and controlled process that promotes cell growth and death. Inducing apoptosis is an important strategy to control excessive breast cancer cell proliferation. Accumulating evidence has revealed that natural products become increasingly important in breast cancer treatment by suppressing cell apoptosis. In this study, we reviewed current studies on natural product-induced breast cancer cell apoptosis and summarized the pro-apoptosis mechanisms including mitochondrial, FasL/Fas, PI3K/AKT, ROS, and MAPK-mediated pathway. We hope that our review can provide direction in the search for candidate drugs derived from natural products to treat breast cancer by promoting cell apoptosis.